Income protection of atypical workers in the event of unemployment in Europe - H. Xavier Jara; Alberto Tumino (University of Essex, Institute for Social and Economic Research (ISER), 2018)
This paper evaluates the degree of income protection the tax-benefit system provides to atypical workers in the event of unemployment, comparing them to standard employees. Our approach relies on EUROMOD, the EU tax-benefit microsimulation model, to simulate transitions from employment to unemployment for the entire workforce and to compare household financial circumstances before and after the transition. Our results show that coverage rates of unemployment insurance are low among atypical workers. These workers are also significantly more exposed to the risk of poverty than standard employees, both while in work and in the event of unemployment. Our analysis also shows that low-work intensity employees are characterised by higher net replacement rates than other groups. However, this is due to the major role played by the market incomes of other household members. Finally, we show that in countries where self-employed workers are not eligible for unemployment insurance benefits, extending the eligibility to this group of workers would increase their replacement rates significantly and make them less likely to fall into poverty in the event of unemployment.
Keywords: C81; H55; I3; 330; income protection; atypical work; microsimulation